1983
DOI: 10.1152/ajpheart.1983.244.3.h362
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary reflexes and arterial pressure during rest and exercise in dogs

Abstract: Mean arterial blood pressure, heart rate, and cardiac output were monitored at rest and during exercise of two grades of severity in conscious dogs under control conditions and after progressive interruption of the baroreflexes. Aortic arch denervation and vascular isolation and pressurization of the carotid sinuses were used to interrupt arterial baroreflexes. Subsequent interruption of cardiopulmonary afferents was produced by acute bilateral cervical vagotomy. The results indicate that 1) with the cardiopul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Moreover, the ABR, together with central command and the exercise pressor reflex play an essential role in evoking appropriate neural cardiovascular responses to exercise. Indeed, sinoaortic denervation and reductions in ABR control have been shown to lead to exaggerated elevations in BP upon exercise (6,56,57). Thus appropriate ABR resetting and function are requisite for normal BP responses to dynamic exercise (14,26,46,47).…”
mentioning
confidence: 99%
“…Moreover, the ABR, together with central command and the exercise pressor reflex play an essential role in evoking appropriate neural cardiovascular responses to exercise. Indeed, sinoaortic denervation and reductions in ABR control have been shown to lead to exaggerated elevations in BP upon exercise (6,56,57). Thus appropriate ABR resetting and function are requisite for normal BP responses to dynamic exercise (14,26,46,47).…”
mentioning
confidence: 99%
“…First, Thoren 39 suggests that the slowly reacting cardiopulmonary receptors seem to be relatively insensitive to the mbment-to-moment changes in blood pressure seen after baroreceptor denervation. Second, Walgenbach and Donald 36 recently showed that cardiopulmonary deafferentation did not affect the lability of the arterial pressure in dogs, in either the presence or absence of functioning arterial baroreceptor reflexes. Therefore, it is doubtful that concomitant destruction of the baroreceptor and cardiopulmonary reflexes contributed markedly to the differences in the lability of arterial pressure of the SAD and NTS groups.…”
mentioning
confidence: 99%
“…3839 Kezdi et al 38 have shown increased C-fiber activity from cardiopulmonary receptors after SAD in dogs and suggest this may be sufficient to return pressure to normal or near normal levels. However, Walgenbach and Donald 36 found that, although cardiopulmonary reflexes do exert tonic vasomotor inhibition, this is insufficient to maintain pressure near normal levels in the absence of the arterial baroreceptor reflexes. Furthermore, if damage to the cardiopulmonary reflexes accounted for the mild hypertension in some rats after SAD, then the arterial pressure of all rats with NTS lesions should be similarly elevated, since vagal afferents project densely to the area of the NTS that is consistently destroyed by the lesions.…”
mentioning
confidence: 99%
“…In the 1980s, David Donal's group at the Mayo Clinic performed a series of investigations using treadmill exercising canines with and without surgically isolated carotid sinus in combination with or without vagotomy (20,64,109,110). The major finding of these studies were that 1) the carotid-HR reflex was reset to a higher OP pressure in association with the increasing exercise intensities and 2) vagal afferent neural information from cardiopulmonary baroreceptors was important for establishing the resetting of the OP pressure.…”
Section: Arterial Baroreflexmentioning
confidence: 99%
“…The current model of circulatory control during exercise holds that it is governed by two main neural mechanisms: 1) the central command (CC), a feedforward control mechanism that sets the basic pattern of motor activity to skeletal muscles and drives cardiorespiratory activation (22,33,62,70), and 2) the feedback control mechanisms driven by intrinsic/extrinsic receptors from cardiovascular areas and receptors within the active muscles (57,71,95,109).…”
mentioning
confidence: 99%